Modified bismuth-based catalyst as well as preparation method and application thereof
By hybridizing boron-doped carbon oxide material with oxidized bismuth-based catalyst, a modified bismuth-based catalyst is formed, which solves the problem that the active sites of bismuth-based catalysts are prone to dynamic changes during the carbon dioxide electroreduction process, and achieves efficient and stable carbon dioxide electroreduction performance.
Patent Information
- Application Number
- CN202411812615.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The active sites of existing bismuth-based catalysts are prone to dynamically change during the electroreduction of carbon dioxide, resulting in unstable performance, especially in complex reaction environments.
By hybridizing boron-doped carbon oxide material with oxidized bismuth-based catalyst, a modified bismuth-based catalyst is formed to enhance its hydrophobic properties, and the in-situ synthesis and advanced construction of Bi−O−C structure is promoted to promote the non-reversible reconstitution of the basic bismuth carbonate.
It significantly improves the carbon dioxide electroreduction performance of the catalyst, achieves high formic acid selectivity, high catalytic efficiency and excellent stability, and can maintain efficient catalysis at high current density.
Smart Images

Figure CN119553309A_ABST
Abstract
Description
Technical Field
[0001] The present technology relates to the field of electrochemical reduction of CO2 catalysis, and specifically to bismuth-based catalysts, preparation methods and their application in the electrochemical reduction of carbon dioxide. Background Art
[0002] Electrochemical CO2 reduction for clean and sustainable energy conversion to electricity represents a technology with great potential to contribute to mitigating the global climate crisis while promoting the recycling of CO2. This process can efficiently convert CO2 into a variety of beneficial chemicals, especially formates / formic acid, which are not only attractive as key intermediates in chemical synthesis, leather, pharmaceutical and textile industries, but also have great potential as hydrogen storage / transport media and as a relatively safe liquid carrier in direct formic acid fuel cells, which has considerable potential for the development of hydrogen technology and the promotion of carbon neutrality.
[0003] In the process of carbon dioxide electroreduction, the product selectivity of various metal active sites is different. For example, metals such as indium (In), tin (Sn), lead (Pb), bismuth (Bi) and mercury (Hg) show high formic acid selectivity. Zhang Biaobiao et al. (2023, Vol. 145, pp. 14101-14111, Journal of the American Chemical Society; Title: Indium Cyanamide for [industrial-Grade CO Electroreduction to Formic Acid.) used linear cyanamide anions and indium to coordinate to construct InNCN catalysts, which showed high selectivity for formic acid at 500 mA cm −2 The Faraday efficiency of formic acid at the current density reached 81.4%; Bao Xinhe et al. (Angewandte Chemie Interational Edition, Vol. 59, pp. 4814-4821; Title: InSitu Reconstruction of a Hierarchical Sn-Cu / SnO x Core / Shell Catalyst for High-Performance CO2 Electroreduction.) x Sn-Cu / SnO shell x The core-shell catalyst has a high conductivity at 243 mA cm −2 The Faradaic efficiency of formic acid reaches 90% at the current density.
[0004] In this context, bismuth-based catalysts have attracted extensive attention due to their low toxicity, easy availability, and environmental friendliness. In addition, their low side-reaction hydrogen evolution activity and good affinity for the key intermediate *OCHO in the formation of formic acid make them highly selective in the electroreduction of carbon dioxide to formate / formic acid. Therefore, corresponding electrocatalysts have been developed for this process. For example, defects were fabricated on bismuth oxide nanotubes (NTD-Bi) and the electrocatalytic activity was significantly increased at 140 mA cm −2 The Faradaic efficiency of formic acid reaches 95% at a current density of 95% (Nature Communications, Vol. 10, p. 2807, 2019; Title: Structural defects on converted bismuth oxide nanotubes enable highly active electrocatalysis of carbondioxide reduction). However, the influence of complexity and variability in the actual reaction environment, especially for bismuth-based catalysts during carbon dioxide electroreduction, can lead to dynamic changes in active sites. Specifically, bismuth-based catalysts may spontaneously undergo irreversible reconstruction to form bismuth subcarbonate in a carbonate aqueous electrolyte. Studies have confirmed that this bismuth subcarbonate exhibits excellent performance in the catalytic process of carbon dioxide electroreduction to formic acid.
[0005] Due to their unique properties, such as diverse pore structures, adjustable chemical compositions, and easily modifiable surface groups, carbon materials can effectively form and stabilize highly dispersed active sites when hybridized with bismuth species, thereby improving electron transfer and regulating electronic structure, thereby regulating the affinity for reactants / intermediates / products. This hybridization strategy provides a broad approach to improving catalyst performance.
[0006] In addition, heteroatom doping is a commonly used strategy in the study of improving catalyst performance. For example, doping with boron (B), nitrogen (N), and sulfur (S) has been widely studied and proven to significantly improve catalyst performance. In particular, boron doping has been shown to enhance the hydrophobicity of the catalyst. During the CO2 electroreduction process, especially in the flow cell, highly hydrophobic catalysts can better contact with CO2, increase the mass transfer rate, and thus improve the CO2 electroreduction performance. Summary of the invention
[0007] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a modified bismuth-based catalyst. Another technical problem to be solved by the present invention is to provide and analyze a modified bismuth-based catalyst product. The last technical problem to be solved by the present invention is to provide an application of carbon dioxide electro-reduction of the modified bismuth-based catalyst. The modified bismuth-based catalyst provided by the present invention improves the hydrophobic properties of the catalyst, thereby significantly enhancing its performance of carbon dioxide electro-reduction.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A modified bismuth-based catalyst is formed by a boron-doped oxidized carbon material and an oxidized bismuth-based catalyst.
[0009] Preferably, the oxidized bismuth-based catalyst is bismuth oxide, bismuth basic carbonate, or a combination of the first two or a generated bismuth oxide, and the oxidized carbon material is oxidized carbon black, oxidized graphene, oxidized carbon nanotubes or oxidized carbon fibers.
[0010] Preferably, the molar content of elemental bismuth in the oxidized bismuth-based catalyst is 10% to 30%; the molar ratio of the oxidized carbon material to the oxidized bismuth-based catalyst is 1:1 to 10.
[0011] Preferably, the modified bismuth-based catalyst is formed by boron-doped oxidized carbon black and bismuth oxide; boron-doped oxidized carbon black and bismuth basic carbonate; boron-doped oxidized carbon black and bismuth oxide and bismuth basic carbonate in combination; boron-doped oxidized graphene and bismuth oxide; boron-doped oxidized carbon nanotubes and bismuth oxide.
[0012] A method for preparing a modified bismuth-based catalyst comprises the following steps: (1) mixing a carbon material and an aqueous nitric acid solution to obtain an oxidized carbon material; (2) mixing the prepared oxidized carbon material with boric acid to obtain a boron-doped oxidized carbon material; (3) The oxidized bismuth-based catalyst is mixed with the boron-doped oxidized carbon material to obtain the final product.
[0013] Preferably, the mixing of the oxidized bismuth-based catalyst and the boron-doped oxidized carbon material in step (3) is performed by mixing bismuth nitrate with the boron-doped oxidized carbon material under the action of dimethylimidazole or by mixing bismuth trioxide with the boron-doped oxidized carbon material to obtain the final product.
[0014] Preferably, the nitric acid aqueous solution in step (1) is an aqueous solution with a nitric acid mass fraction of 20-60%. Step (1) requires heating and stirring for oxidation at a temperature of 75-85°C. Step (2) is performed by high-temperature pyrolysis in a nitrogen atmosphere at a temperature of 800-1000°C. Step (3) requires stirring at a temperature of 15-25°C.
[0015] Preferably, the nitric acid aqueous solution in step (1) refers to an aqueous solution with a mass fraction of nitric acid of 40%; the carbon material is carbon black, and the carbon black model is superconducting K90 or Ketjenblack EC 600 JD superconducting carbon black; heating, stirring and oxidation are required in step (1), and the required temperature is 80°C; The conditions of high temperature pyrolysis in nitrogen atmosphere in step (2) are 1000°C for 2 h; the mass ratio of the oxidized carbon black to the boric acid is 2: (1-4); The mass ratio of the boron-doped carbon black oxide, bismuth nitrate and dimethylimidazole in step (3) is 1:12:(10-16); the stirring time of the two solutions is 48 h; and the stirring temperature is 20°C.
[0016] The modified bismuth-based catalyst of the present invention is used as a catalyst in the electroreduction of carbon dioxide.
[0017] Preferably, when electrocatalytic reduction of carbon dioxide is performed to generate formic acid, a silver-silver chloride electrode is used as a reference electrode and a platinum sheet or iridium oxide is used as an auxiliary electrode; the carbon dioxide-saturated aqueous electrolyte includes carbon dioxide-saturated KOH solution, NaHCO3 solution, KHCO3 solution, RbHCO3 solution, CsHCO3 solution, Na2CO3 solution, K2CO3 solution, KOH solution, CsOH solution, and LiOH solution.
[0018] Beneficial effects: The modified bismuth-based catalyst provided by the present invention constructs a special catalyst structure: by hybridizing boron-doped oxidized carbon black with bismuth oxide, the in-situ synthesis of bismuth oxide and the advance construction of Bi-O-C structure are realized, and the advance construction of Bi-O-C structure effectively promotes the non-reversible reconstruction of bismuth basic carbonate during the carbon dioxide electroreduction process. In particular, during the carbon dioxide electroreduction process, bismuth oxide will partially spontaneously and irreversibly reconstruct into bismuth basic carbonate (Bi2O2CO3), forming bismuth basic carbonate composite bismuth oxide (Bi2O2CO3 / Bi2O3). The existence of this structure significantly improves the application performance of the catalyst in carbon dioxide electroreduction. In the process of boron-doped oxidized carbon black in situ reconstruction of bismuth species into bismuth basic carbonate during carbon dioxide electroreduction, additional Bi-O-C interactions are provided for the formation and stabilization of the rich Bi-O structure, thereby preparing the final catalyst: bismuth basic carbonate composite bismuth oxide (Bi2O2CO3 / Bi2O3).
[0019] The modified bismuth-based catalyst of the present invention exhibits high formic acid selectivity, high catalytic efficiency, excellent stability and high working current capability in carbon dioxide electroreduction. −2 The Faradaic efficiency of formic acid can still reach 95.2% at a current density of 100 mAcm in a membrane electrolyzer. −2 The reaction can be carried out stably for 12 h at a current density of 1.547 W / m, and the Faradaic efficiency of formic acid is still greater than 82%.
[0020] The present invention also provides a method for preparing a modified bismuth-based catalyst, through which boron doping significantly improves the hydrophobicity and conductivity of the composite catalyst, increases the mass transfer rate, accelerates electron transfer and inhibits the side reaction of the hydrogen evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of Bi@BOC synthesis; Figure 2 Bi@BOC and comparative samples Bi@OC, BiO x XRD pattern of Figure 3 Bi@BOC and comparative samples Bi@OC, BiO x Nitrogen adsorption-desorption curve and pore size distribution diagram; Figure 4 (a) SEM image of Bi@BOC sample, (b) SEM image of Bi@OC sample, (c) SEM image of BiO x SEM images of Figure 5 (a) Samples Bi@BOC, Bi@OC, BiO x and the Bi- L 3 Edge X-ray absorption near-edge absorption spectra, (b) samples Bi@BOC, Bi@OC, BiO x and the Bi- L 3 Edge x-ray absorption expands edge absorption spectra; Figure 6 (a) Contact angle test of sample Bi@BOC, (b) Contact angle test of sample Bi@OC; Figure 7 Bi@BOC in flow cell configuration at 800 mA cm −2 After the carbon dioxide electroreduction reaction was carried out at a current density of 0.5 h, the electrolyte 1 H NMR spectrum; Figure 8is the Faraday efficiency of each product of Bi@BOC at different current densities; Fig. 9 This is a diagram of the stability performance test of Bi@BOC in a membrane reactor; Fig.10 In-situ XAFS diagram of Bi@BOC during carbon dioxide electroreduction; Fig.11 In situ ATR-SEIRAS spectrum of Bi@BOC during carbon dioxide electroreduction; Fig.12 XRD pattern of the working electrode coated with Bi@BOC after the fresh electrode and carbon dioxide electroreduction reaction; Fig.13 (a) High-resolution Bi 4f XPS spectra of Bi@BOC catalyst before and after the reaction on the working electrode, (b) High-resolution O 1s XPS spectra of Bi@BOC catalyst before and after the reaction on the working electrode, (c) High-resolution C 1s XPS spectra of Bi@BOC catalyst before and after the reaction on the working electrode; Fig.14 This is a performance comparison chart of Bi@BOC and reported related catalysts for carbon dioxide electroreduction to formic acid. DETAILED DESCRIPTION
[0022] To facilitate the technical solution of the application, some concepts involved in the application are first explained below.
[0023] Example 1 Carbon black (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black. Oxidized carbon black (0.2 g) and boric acid (0.1 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon black was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0024] Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then boron-doped oxidized carbon black (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@BOC.
[0025] Example 2 Carbon black (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black. Oxidized carbon black (0.2 g) and boric acid (0.2 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon black was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0026] Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then boron-doped oxidized carbon black (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@BOC-1.
[0027] Example 3 Carbon black (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black. Oxidized carbon black (0.2 g) and boric acid (0.4 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon black was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0028] Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then boron-doped oxidized carbon black (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@BOC-0.5.
[0029] Example 4 Carbon black (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black. Oxidized carbon black (0.2 g) and boric acid (0.1 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon black was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0030] Bismuth subcarbonate (3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated, and then boron-doped carbon black oxide (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample, which was recorded as Bi2O2CO3@BOC.
[0031] Example 5 Carbon black (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black. Oxidized carbon black (0.2 g) and boric acid (0.1 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon black was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0032] Bismuth subcarbonate (1.5 mmol) and bismuth trioxide (1.5 mmol) were dissolved in 60 mL N, N-dimethylformamide and sonicated, and then boron-doped carbon black oxide (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample, which was recorded as Bi2O3-Bi2O2CO3@BOC.
[0033] Example 6 Graphene (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain graphene oxide. Graphene oxide (0.2 g) and boric acid (0.1 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped graphene oxide was obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0034] Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then boron-doped graphene oxide (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@BOC-Graphene.
[0035] Example 7 Multi-walled carbon nanotubes (2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon nanotubes. Oxidized carbon nanotubes (0.2 g) and boric acid (0.1 g) were mixed in a mortar and ground thoroughly to obtain a relatively uniform powder. The mixture was transferred to a porcelain boat and placed in a tube furnace. Boron-doped oxidized carbon nanotubes were obtained by pyrolysis at 1000 °C for 2 h under a nitrogen flow.
[0036] Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then boron-doped oxidized carbon nanotubes (0.1 g) were added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@BOC-MWNT.
[0037] Comparative Example 1 Carbon black (0.5073 g, 2.1 mmol) and aqueous nitric acid solution (40 wt%, 50 mL) were mixed in a 100 mL flask, and the mixture was stirred in a water bath at 80 °C for 24 h. After that, the solid was separated by filtration, washed with deionized water, and dried in an oven at 70 °C to obtain oxidized carbon black.
[0038] Bismuth nitrate (3 mmol) was dissolved in 50 mL of methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL of N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min, and then oxidized carbon black (0.1 g) was added. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as Bi@OC.
[0039] Comparative Example 2 Bismuth nitrate (3 mmol) was dissolved in 50 mL methanol and sonicated for 30 min to obtain solution A. Dimethylimidazole (17.3 mmol) was dissolved in 60 mL N, N-dimethylformamide and sonicated to obtain solution B. Solutions A and B were mixed and stirred for 10 min. The mixture was stirred at room temperature for 48 h. Subsequently, the solid was separated by centrifugation, washed with methanol, and dried in an oven at 70 °C to obtain the final sample recorded as BiO x .
[0040] Test Example 1 The sample display flow chart of Example 1 is as follows Figure 1 As shown: Figure 1 This is a simplified diagram of the synthesis of the sample of Example 1, showing the hybridization process of boron-doped carbon black oxide and bismuth oxide.
[0041] Test Example 2 The samples of Examples 1-3 and the comparative example were subjected to structural characterization and related performance tests. The results are as follows: Figure 1-4 As shown: Figure 2 3 are the XRD patterns of the sample of Example 1 and the samples of Comparative Examples 1 and 2. The three samples show a diffraction peak at 27.98°, corresponding to the (221) crystal plane of Bi2O3, proving the existence of the Bi2O3 structure.
[0042] Figure 3The nitrogen adsorption-desorption curves and pore size distribution diagrams of the sample in Example 1 and the samples in Comparative Examples 1 and 2 show that the nitrogen adsorption isotherms of the synthesized samples are of type I+IV, with a relatively small sharp absorption at low pressure, corresponding to the presence of micropores, and a flat and high absorption at high pressure, reflecting the presence of abundant mesopores and macropores. Accordingly, the Bi@BOC in Example 1 has the largest surface area (201 m 2 g −1 The surface area of the pore volume is 0.13 cm 3 g −2 ).
[0043] Figure 4 It is the SEM picture of the sample of Example 1 and the comparative example sample. Figure 4 (a) SEM image of Bi@BOC sample, (b) SEM image of Bi@OC sample, (c) SEM image of BiO x SEM images of the samples. The samples are composed of primary particles with a size of tens of nanometers. Loose stacking was observed on these carbon-based hybrid materials, while in Comparative Example 2 BiO x A slightly tighter packing was found on
[0044] Figure 5 The XAFS graphs of the sample in Example 1, the comparative sample and the Bi2O3 standard sample are shown in FIG. Figure 5 (a) Samples Bi@BOC, Bi@OC, BiO x and the Bi- L 3 Edge X-ray absorption near-edge absorption spectra, (b) samples Bi@BOC, Bi@OC, BiO x and the Bi- L 3 Edge x-ray absorption expands the edge absorption spectrum. Figure 5 XAFS can be used to analyze the valence state of metal Bi and the coordination environment around metal Bi. In the figure, the three samples show Bi- L 3 The X-ray absorption near-edge structure (XANES) spectra show that the oxidation state of the bismuth species is close to +3. L 3 The edge shows a distinct peak at R = 2.18 Å, which is attributed to the Bi−O scattering path.
[0045] exist Figure 6 In the embodiment 1, we compared the contact angles of the samples of the comparative example 1. Figure 6(a) Contact angle test of sample Bi@BOC, (b) Contact angle test of sample Bi@OC. It is worth noting that after boron doping, the contact angle of Example 1 is significantly increased from the initial 26° to about 67°. This change fully demonstrates that the hydrophobicity of Bi@BOC in Example 1 is significantly enhanced compared with Bi@OC in Comparative Example 1.
[0046] Test Example 3 The samples prepared in Examples 1-3 and the comparative example were subjected to carbon dioxide electroreduction reaction, and the reaction equations were as follows: cathode: anode: Electrochemical CO2 reduction was performed on a CHI760E electrochemical workstation (Chenhua, Shanghai, China). A flow cell configuration consisting of a working electrode and a carbon paper substrate (1 cm × 3 cm) uniformly coated with the catalyst, an Ag / AgCl reference electrode in 1 M KOH, and a platinum counter electrode (1 cm × 3 cm) was used. The volume of the cathode and anode compartments was 100 mL, and the two compartments were separated by an anion exchange membrane (AEM, PiperION-A20-HCO3). The area of the working electrode, counter electrode, and anion exchange membrane was 1 cm −2 .
[0047] The working electrode (cathode) was prepared as follows: the catalyst (3 mg) was mixed with Nafion solution (5% w / v, 0.03 mL) and isopropanol (0.3 mL) by ultrasonication for 30 min to prepare catalyst ink. Then, 0.33 mL of the ink was coated on carbon paper with a coating area of 1 × 3 cm 2 , the catalyst loading was 1 mg cm −2 The electrode was dried at 40 °C to obtain a working electrode.
[0048] In the cathode and anode compartments, 50 mL of 1 M potassium bicarbonate (KHCO3) was added as electrolyte. Before the electrolysis experiment, high-purity carbon dioxide (99.9999%, 70 mL min −1 ) was continuously passed through the flow cell for 5 min to remove air from the system. Subsequently, electrolysis was performed using a constant current method. The current density (J) was normalized to the geometric area of the working electrode.
[0049] By using the equation E (V vs. RHE) = E (V vs.Ag / AgCl) + 0.1989 V + 0.0592×pH, rescale the potential applied to the Ag / AgCl reference electrode to the reversible hydrogen electrode (RHE). Calculate the Faradaic efficiency (FE) of the product according to the following formula: in z is the number of transferred electrons of the target product (formate z = 2); n is the actual number of moles of the target product, mol; F is the Faraday constant, 96485 C×mol −1 ; Q is the electrolysis power, C.
[0050] Formate ( j formate ) is calculated by using the following formula: in j total is the total current density, S is the reaction area (S = 1 cm −2 ).
[0051] The long-term stability of CO2 electroreduction to formate was evaluated in a two-electrode membrane electrode assembly (MEA) flow electrolyzer separated by an anion exchange membrane (AEM, PiperION-A20-HCO3). The cathode electrode was formed by a YLS-30T GDL electrode (2×2 cm 2 ) loaded with 1 mg cm −2 The catalyst was prepared, and the anode electrode was an iridium oxide mesh (2×2 cm 2 The cathode side was supplied with a carbon dioxide gas stream filled with water (20 mL min −1 ). The electrolyte on the anode side was heated at 5 mL min −1 The CO2RR in the MEA system is conducted by constant flow test. In this device, the cathode is filled with water vapor and carbon dioxide gas flow, which isolates the influence of cathode electrolyte and the influence of gas mass transfer resistance. It is a promising device for improving stability and industrialization.
[0052] Figure 7 The Bi@BOC in Example 1 was used in a flow cell configuration at 800 mA cm −2 After the carbon dioxide electroreduction reaction was carried out at a current density of 0.5 h, the electrolyte 1 H nuclear magnetic resonance (NMR) spectrum. This spectrum not only confirms the generation of formic acid, but also quantitatively analyzes its content.
[0053] Table 1: Summary of the CO2 electroreduction current density, voltage and formate Faraday efficiency of the catalysts One indicator for judging the performance of carbon dioxide electroreduction is to have a high product Faraday efficiency at the largest possible current. Table 1 shows the carbon dioxide electroreduction current density, voltage and formate Faraday efficiency of the catalyst, proving that Example 1 Bi@BOC exhibits excellent activity in the carbon dioxide electroreduction process, and its current density, voltage and formate Faraday efficiency are better than those of the comparative example. By comparing Example 1 Bi@BOC with Comparative Example 2 Bi@OC, we found that the introduction of element B significantly improved the catalyst's ability to produce formic acid, although at a current below 600 mA cm −2 The performance of the two catalysts is similar when the current density is greater than 600 mA cm −2 The boron-doped samples have better stability at 800 mA cm due to their high hydrophobicity. −2 The formic acid Faraday efficiency can still reach 95.2% at a current density of . Further, by comparing Example 1 Bi@BOC with Example 2 Bi@BOC-1 and Example 3 Bi@BOC-2, it can be seen that the Faraday efficiency of Examples 2 and 3 at the corresponding current density has a very large decrease, which indicates that excessive doping of B element is not conducive to the formation of formate, and the performance of the catalyst will be negatively affected. In particular, the performance of Comparative Example 1 Bi@OC is significantly better than that of Comparative Example 2 BiO x , which is attributed to the addition of carbon black and bismuth oxide hybridization, which greatly improves the overall performance of the catalyst.
[0054] Figure 8 The Faradaic efficiency of each product of the optimal example 1 Bi@BOC at different current densities is shown. It can be seen that in the range of 300-800 mA cm −2 Example 1 has high Faradaic efficiency of formic acid over a wide voltage range.
[0055] Fig. 9 The optimal example 1 Bi@BOC was tested for stable performance in an anion exchange membrane electrolyzer (MEA) at 100 mA cm −2 After 12 h of continuous electrolysis at -3.5 V, the Faradaic efficiency of formic acid was still higher than 82%.
[0056] Test Example 4 The sample of Example 1 was subjected to in-situ real-time structural characterization of carbon dioxide electroreduction reaction.
[0057] Fig.10The in situ X-ray absorption spectroscopy (XAFS) was used to test and analyze the carbon dioxide electroreduction process of Example 1 Bi@BOC. Extensive studies have shown that catalyst reconstruction in carbon dioxide is very complex. The use of in situ spectroscopy techniques can provide in-depth research on the catalyst. Operate XAFS to measure the conversion of carbon dioxide to formate by Bi@BOC, with an applied voltage range of 0 V to −1 V vs. RHE. Collect Bi- L 3 Edge XANES spectrum. It can be seen from the figure that when the applied potential changes from open circuit state (OCP) to 0 V vs. During RHE, Bi- L 3 The absorption edge shifts to lower energy, reflecting the decrease in oxidation state.
[0058] When the potential shifts negatively from 0 V to −0.2 V relative to RHE vs. During RHE, Bi- L 3 The edge shifts to higher energies. This indicates that the formed low-valent bismuth species are consumed during the CO2 electroreduction and return to their original state. As the potential is further increased to −1.0 V vs. RHE, Bi- L 3 The edge shifts to lower energy due to the partial reduction of Bi species at very negative potentials. L 3 The edge Bi@BOC (spectra collected after 5 min when the applied potential was switched to the open-circuit state) quickly recovered to the open-circuit state, indicating that the hybridization of BCB with Bi oxide contributes to the CO2 activity and stability of the catalyst and the reversibility of the Bi species.
[0059] Fig.11 In situ ATR-SEIRAS spectra of the Bi@BOC sample of Example 1 were collected to monitor the structural changes of the catalyst and the formation of reaction intermediates during the CO2 electroreduction. During the CO2 electroreduction process, as the voltage increased, we observed a peak at 1236 cm −1 A negative peak was observed at − Consumption of HCO3 − The formation of bismuth subcarbonate is favorable, while at 1100 cm −1 and 1509 cm −1 The peaks at 2−, which is essential for the irreversible reconstruction of the bismuth species into bismuth subcarbonate, further confirming the formation of bismuth subcarbonate. −1 No corresponding peak was observed at , which indicates that Bi@BOC has a higher CO barrier and is therefore less likely to generate by-product CO.
[0060] Test Example 5 In the process of carbon dioxide electroreduction, Nafion is used to load the catalyst on carbon paper as the working electrode, and the catalyst usually undergoes structural reconstruction after the potential is applied. In order to gain a deeper understanding of this process, the working electrode coated with the catalyst (Example 1) was characterized by XRD and XPS before and after the reaction.
[0061] Fig.12 Comparison of the XRD spectra of the fresh electrode and the electrode after the reaction shows that the latter has obvious peaks corresponding to bismuth basic carbonate. This indicates that Bi@BOC has undergone irreversible structural evolution and produced bismuth basic carbonate as an active site during the carbon dioxide electroreduction process.
[0062] Fig.13 The XPS spectra of fresh electrodes and electrodes after reaction are shown. Fig.13 (a) High-resolution Bi 4f XPS spectra of Bi@BOC catalyst before and after the reaction, (b) High-resolution O 1s XPS spectra of Bi@BOC catalyst before and after the reaction, (c) High-resolution C 1s XPS spectra of Bi@BOC catalyst before and after the reaction. In the Bi 4f XPS spectrum, the peak of bismuth basic carbonate appears; in the O 1s XPS spectrum, the signal of Bi−O increases relatively; in addition, the signal of C=O also appears in the C 1s XPS spectrum. These changes all indicate the formation of bismuth basic carbonate.
[0063] Test Example 6 Table 2 is a comparative table of the performance of Example 1 and related reported catalysts for the electroreduction of carbon dioxide to formic acid in potassium bicarbonate (KHCO3) electrolyte * Voltage refers to iR compensation.
[0064] Fig.14 The performance comparison table of Example 1 and related reported catalysts for producing formic acid by carbon dioxide electroreduction is expressed in the form of a picture, which proves that Example 1 has excellent performance in carbon dioxide electroreduction.
[0065] The sources of existing catalyst literature are as follows: ① Catalyst Bi-DC; Source: ACS Catalysis 2024; Title: Beyond Leverage in Activity and Stability toward CO2 Electroreduction to Formate over a Bismuth Catalyst. ② Catalyst InNCN; Source: 2023 Journal of the American Chemical Society; Title: Indium Cyanamide for Industrial-Grade CO2 Electroreduction to Formic Acid. ③ Catalyst NTD-Bi; Source: Nature Communications, 2019; Title: Structural defects on converted bismuth oxide nanotubesenable highly active electrocatalysis of carbon dioxide reduction. ④ Catalyst Bi@Sn; Source: Advanced Science 2020; Title: Bi@Sn Core–Shell Structure with Compressive Strain Boosts the Electroreduction of CO2into Formic Acid. ⑤ Catalyst ZnIn2S4; Source: Nature Communications, 2021; Title: Stabilizing indium sulfide for CO2 electroreduction to formate at high rate by zinc incorporation. ⑥ Catalyst L-In; Article source: 2022 Small; Title: Transient Solid-State Laser Activation of Indium for High-Performance Reduction of CO2 to Formate. ⑦ Catalyst Ni-In2O3@C NFs; Source: ACS Catalysis 2021; Title: In Situ Carbon Encapsulation Confined Nickel-Doped Indium Oxide Nanocrystals for Boosting CO2 Electroreduction to the Industrial Level. ⑧ Catalyst Sn 2.7 Cu / SnO2; Source: Angewandte Chemie International Edition 2020; Title: In Situ Reconstruction of a Hierarchical Sn-Cu / SnO x Core / ShellCatalyst for High-Performance CO2Electroreduction. ⑨ Catalyst Sn3O4; Source: Nano Energy 2020; Title: Tuning Sn3O4forCO2reduction to formate with ultra-high current density.
Claims
1. A modified bismuth-based catalyst, characterized in that The modified bismuth-based catalyst is formed by boron-doped oxidized carbon material and oxidized bismuth-based catalyst.
2. The modified bismuth-based catalyst according to claim 1, characterized in that: The oxidized carbon material is oxidized carbon black, oxidized graphene, oxidized carbon nanotubes or oxidized carbon fibers; the oxidized bismuth-based catalyst is bismuth oxide, bismuth basic carbonate or a combination of the first two or a generated bismuth oxide.
3. The modified bismuth-based catalyst according to claim 1 or 2, characterized in that: The molar content of elemental bismuth in the oxidized bismuth-based catalyst is between 10% and 30%; the molar ratio of the oxidized carbon material to the oxidized bismuth-based catalyst is between 1:1 and 10.
4. The modified bismuth-based catalyst according to claim 1 or 2, characterized in that: The modified bismuth-based catalyst is formed by boron-doped oxidized carbon black and bismuth oxide; boron-doped oxidized carbon black and bismuth basic carbonate; boron-doped oxidized carbon black, bismuth oxide and bismuth basic carbonate in combination; boron-doped oxidized graphene and bismuth oxide; and boron-doped oxidized carbon nanotubes and bismuth oxide.
5. A method for preparing a modified bismuth-based catalyst, characterized in that: Here are the steps: (1) mixing a carbon material and an aqueous nitric acid solution to obtain an oxidized carbon material; (2) mixing the prepared oxidized carbon material with boric acid to obtain a boron-doped oxidized carbon material; (3) The oxidized bismuth-based catalyst is mixed with the boron-doped oxidized carbon material to obtain the final product.
6. The preparation method according to claim 5, characterized in that: The mixing of the oxidized bismuth-based catalyst and the boron-doped oxidized carbon material in step (3) is performed by mixing bismuth nitrate with the boron-doped oxidized carbon material under the action of dimethylimidazole or by mixing bismuth trioxide with the boron-doped oxidized carbon material to obtain the final product.
7. The preparation method according to claim 5, characterized in that: The nitric acid aqueous solution described in step (1) is an aqueous solution with a nitric acid mass fraction of 20-60%. Step (1) requires heating and stirring oxidation at a temperature of 75-85°C. Step (2) is high-temperature pyrolysis in a nitrogen atmosphere at a temperature of 800-1000°C. Step (3) requires stirring at a temperature of 15-25°C.
8. The preparation method according to claim 5, characterized in that: The nitric acid aqueous solution described in step (1) refers to an aqueous solution with a mass fraction of nitric acid of 40%; the carbon material is carbon black, and the carbon black model is superconducting K90 or Ketjenblack EC 600 JD superconducting carbon black; heating, stirring and oxidation are required in step (1), and the required temperature is 80°C; The conditions of high temperature pyrolysis in nitrogen atmosphere in step (2) are 1000°C for 2 h; the mass ratio of the oxidized carbon black to the boric acid is 2: (1-4); The mass ratio of the boron-doped carbon black oxide, bismuth nitrate and dimethylimidazole in step (3) is 1:12:(10-16); the stirring time of the two solutions is 48 h; and the stirring temperature is 20°C.
9. The modified bismuth-based catalyst according to any one of claims 1 to 4 and the use of the modified bismuth-based catalyst prepared according to claims 5 to 8, characterized in that: The modified bismuth-based catalyst is used as a catalyst in the electroreduction of carbon dioxide.
10. The use according to claim 9, characterized in that: When carbon dioxide is electrocatalytically reduced to generate formic acid, a silver-silver chloride electrode is used as a reference electrode, and a platinum sheet or iridium oxide is used as an auxiliary electrode; the carbon dioxide-saturated aqueous electrolyte includes carbon dioxide-saturated KOH solution, NaHCO3 solution, KHCO3 solution, RbHCO3 solution, CsHCO3 solution, Na2CO3 solution, K2CO3 solution, KOH solution, CsOH solution, and LiOH solution.
Citation Information
Patent Citations
Composite catalyst with mono-disperse metal atoms being loaded on graphene / carbon nano tube and preparation method and application of composite catalyst
CN107829107A
Bismuth-based catalyst for electrocatalytic CO2 reduction to form formic acid and preparation method and application thereof
CN109518222A
Bismuth-based electrocatalyst with hierarchical structure, preparation of bismuth-based electrocatalyst and application of bismuth-based electrocatalyst in electroreduction of carbon dioxide
CN115011993A
Preparation method of novel bismuth-based electrode material for electrocatalytic carbon dioxide reduction
CN116103680A
Method for producing formic acid by reducing carbon dioxide through electro-catalysis
CN118272839A
Cited By
Lanthanum carbonate nanotube, copper indium sulfide nanoparticle and balsa wood ternary heterojunction composite catalyst and preparation method and antibiotic degradation application thereof
CN121060578A
A lanthanum oxide carbonate nanotube, indium copper sulfide nanoparticle and balsa wood ternary heterojunction composite catalyst, and a preparation method and antibiotic degradation application thereof
CN121060578B